Amyloidosis as a clinical problem (a difficult case of establishing a diagnosis of renal amyloidosis) - Rodionova, V.V.; Turenko, O.A.; Kuzhevsky, I.V.; Tsyhankov, K.V.; Denisenko, O.O.; Razinina, Yu.O.; Boiko, O.O. (KIDNEYS, 2021)
Amyloidosis is one of the most complex diseases in therapeutic practice and can lead to irreversible kidney damage with the development of chronic renal failure. Therefore, the issue of timely diagnosis and early treatment of this disease is very relevant. The article presents a clinical case of renal amyloidosis.